Rompi Pintar Pengendara Menggunakan Sensor Kemiringan Untuk Kebutuhan Keselamatan Berbasis IOT - Marcelinus Wisnu Ricky Nugroho; Nilla Rachmaningrum; Risdilah Mimma Unsta (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Traffic accidents often occur in everyday life. Many factors cause traffic accidents to occur. Contributors to the high number of traffic accidents are two-wheeled drivers. So an air vest is needed that can reduce the effects of impact if an accident occurs. In this research, an air vest for two-wheeled riders will be designed. Equipped with an IoT-based tilt sensor. This research designs an IoT-based air vest for two-wheeled riders to reduce the impact effects during an accident. This vest is equipped with a tilt sensor which is similar to the function of airbags in four-wheeled vehicles. The way the vest works is that when the sensor detects a certain tilt programmed into the Arduino, the vest will inflate. The main components of this vest are the Arduino Uno ATMega 328 and the MPU-6050 gyroscope sensor. Prototype testing showed a 60% success rate with a development time of 7-10 seconds. However, hands-on testing provided satisfactory results with a 100% success rate and consistent development time of 7-10 seconds. This vest is expected to improve the safety of everyday two-wheeled riders.